Disembodied social life: the ongoing social presence of the born-still on Facebook. (2nd January 2018) - Hayman, Janet; Chamberlain, Kerry; Hopner, Veronica
Abstract: Knowledge about the born-still is the product of multiple and conflicting legal, social, political, religious and medical interpretations. Yet despite their uncertain status, the born-still exist amongst us. Social networks reveal their presence as they progressively escape from social sequestration within family and support groups. Drawing on notions of the intersubjective self and adopting Klass's work on inner representations for the deceased, this paper theorises how the born-still retain a social presence by means of their survivors' internalised relationships with them. Analysis of five Facebook memorial sites created by survivors found substantial support for Klass's theory indicating that survivors were interacting with their inner representations of the child. Some survivors were also found to have developed enduring relationships to the born-still before their death. Importantly, the identities of survivors and the born-still, as well as relationships between them, were reinforced by ongoing engagement of the born-still within social structures and events. Based on the findings in this research, a revised version of Klass's theory of inner representations is proposed. This confirms how prospective, living and deceased others inhabit our minds intersubjectively, challenging understandings of relationships which privilege autonomous embodiment.